Model and experimental-methodical way by definition of time and a current of an anchor of the electromagnetic relay - Бондарук, Т.П.; Гуз, Ю.Т.; Сіткевич, Т.А.; Терехова, М.В. (Proceedings of National Aviation University (archive), 2004)
The mathematical model and the automated system by definition of the moment of time and value of a current of the electromagnetic relay is developed.